The principles of showing man in A. Fadeyev's novel "The Rout" - K. Racevičiūtė (Literatūra (Vilnius))
A. Fadeyev always connected the problem of showing man with that of the formation of the new method, that's why he always tried to find a new principle in solving it. First and foremost he insisted on consequent social-class determination of a character. This principle was the essential one in Fadeyev's novel "The Rout." But the author did not restrict himself only to the revealing of his characters' social-class psychology. The class features are domineering in them, but they are not isolated from other individual qualities, and together with them determine the character of a personage. In that way Fadeyev had achieved the individualization of his characters, avoided schematism. Besides, the individual behaviour of his characters is determined by a different level of their class consciousness. A. Fadeyev's personages are not persons with accomplished characters: the author showed the formation of their class consciousness in detail, revealed the factors by which the process had been influenced.